Penyuluhan perilaku hidup bersih dan sehat (PHBS) melalui cuci tangan pakai sabun (CTPS) kepada siswa SDN Panunggangan 4 sebagai upaya menanamkan nilai bela negara - Audrey Gondokusumo Widjaja; Nicholas; Timotius Enrico Valentino; Ferdy Anthonius; Christian Siregar (Abdimas Altruis: Jurnal Pengabdian kepada Masyarakat, 2026)
Clean handwashing practices are one of the fundamental factors of Clean and Healthy Living Behavior (PHBS), making it essential to instill this habit from an early age. This community service activity aims to increase awareness and the practice of Handwashing with Soap (CTPS) among elementary school students as an effort to implement state defense values and support the Sustainable Development Goals (SDGs) point 3, namely Good Health and Well-Being. The activity was carried out on October 27, 2025, at SDN Panunggangan 4, involving 25 first-grade students as subjects. The methods utilized were interactive lectures, discussions, demonstrations, and the administration of pre-test and post-test questionnaires. Analysis showed that the students' initial level of understanding before the activity averaged 78.1%. After the interactive counseling, there was a significant increase in understanding to 92.1%. This activity successfully enhanced knowledge while instilling awareness that maintaining personal health is a form of concern for the nation's continuity through state defense values.